Influência do mGluR5 e da proteína huntingtina mutante na expressão de genes envolvidos na plasticidade sináptica - Jéssica Mabelle de Souza (2017)
Huntington's disease (DH) is an autosomal dominant neurodegenerative disorder caused by a polyglutamine expansion (> 35 replicates) in the amino-terminal region of the huntingtin protein (htt). Htt has the ability to bind to various transcription factors, such as CREB and REST. However, these interactions are often disrupted in the presence of mutant huntingtin (mhtt). One major change in the cellular physiology triggered by mhtt is the alteration in cell signaling activated via the metabotropic glutamate receptor 5 (mGluR5). mGluR5 plays a dynamic role in the control of gene expression, as it regulates the activity of several transcription factors. Therefore, the aim of this study was to investigate the changes promoted by mGluR5 and mhtt in the expression of genes involved in synaptic plasticity by knocking out mGluR5 expression in a mouse model of HD, the BACHD. Our results demonstrated that mGluR5-/- mice exhibited a lower expression of REST, as compared to wild-type mice. However, expression of REST target genes was influenced not only by mGluR5 but also by mhtt, since BACHD animals exhibited a reduction in expression, whereas animals mGluR5-/- and BACHD/mGluR5-/- showed an increase. In addition, our data indicate that CREB activation and the expression of its target genes are reduced in mGluR5 knockout animals, expressing either wild-type or mhtt. Our results also suggest that there is impairment in synaptic plasticity and in the number of synaptic terminals in BACHD/mGluR5-/- animals, since these animals exhibited a decrease in the expression of genes that are used as pre- and postsynaptic markers, such as syntaxin and PSD95, respectively. In conclusion, this study demonstrates the influence of mGluR5 and mhtt on the expression of genes involved in synaptic plasticity. Morevoer, our data show a dominant interference of mGluR5 in the expression of the analyzed genes, since the BACHD/mGluR5-/- animal follows the same expression pattern as mGluR5-/-. Interestingly, the mGluR5 role in REST expression is a very important finding, as it is a novel finding. Therefore, future experiments will be needed to elucidate the mechanisms underlying the changes observed in BACHD/mGluR5-/- mice.